1986
DOI: 10.1073/pnas.83.6.1941
|View full text |Cite
|
Sign up to set email alerts
|

Fast and slow synaptic potentials produced in a mammalian sympathetic ganglion by colon distension.

Abstract: Radial distension of the large intestine produced a slow depolarization in a population of neurons in the inferior mesenteric ganglion of the guinea pig. The slow potentials often occurred simultaneously with cholinergic fast potentials [(excitatory postsynaptic potentials (EPSPs)] yet persisted in the presence of nicotinic and muscarinic cholinergic antagonists when all fast EPSPs were absent. The amplitude of the distension-induced noncholinergic slow depolarization increased with increasing distension press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…recorded in the guinea-pig i.m.g. in response to repetitive nerve stimulation is also correlated with an increase in membrane resistance (Dun & Jiang, 1982;Peters & Kreulen, 1986). In addition, several putative neurotransmitters including luteinizing hormone releasing hormone (Jan, Jan & Kuffler, 1979) and substance P (Tsunoo, Konishi & Otsuka, 1982) also exhibit an increase in membrane resistance associated with depolarization.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…recorded in the guinea-pig i.m.g. in response to repetitive nerve stimulation is also correlated with an increase in membrane resistance (Dun & Jiang, 1982;Peters & Kreulen, 1986). In addition, several putative neurotransmitters including luteinizing hormone releasing hormone (Jan, Jan & Kuffler, 1979) and substance P (Tsunoo, Konishi & Otsuka, 1982) also exhibit an increase in membrane resistance associated with depolarization.…”
Section: Discussionmentioning
confidence: 93%
“…In recent work on the colon, Peters & Kreulen (1986) demonstrated that colonic distension also gives rise to depolarization and an increase in input resistance in 36 % of cells. The magnitude of depolarization and increase in membrane resistance (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, functions of the ganglia were analyzed by examining the production of NADPH diaphorase and substance P in the neuronal cells. NADPH diaphorase is identical to nitric oxide synthase (26)(27)(28)(29) and nitric oxide functions as an inhibitory neurotransmitter to relax smooth muscle (30), while substance P is an excitatory neurotransmitter to contract circular smooth muscles (31,32). NADPH diaphorase positive neuronal cells were dense in the proximal colon of Ncx Ϫ / Ϫ mice with (data not shown) or without megacolon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(Dun & Jiang, 1982;Tsunoo et al 1982); thus it was a likely candidate for the transmitter of the slow potential produced by colon distension. In a recent study in this laboratory (Peters & Kreulen, 1986) Kreulen, unpublished). .…”
Section: Sp As the Non-cholinergic Transmitter Candidatementioning
confidence: 99%